A single abnormal value of 100 g oral glucose tolerance test and pregnancy outcomes - Kemthong, Walairat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In the worldwide, diabetes mellitus is one of the most common medical complications in pregnancy, the prevalence is about 5% and seems to increase. Objective of this study was to evaluate the effect of a single abnormal value of 100 g OGTT on pregnancy outcomes. Methods: This retrospective cohort study was conducted from January 2014 to December 2018 to identified 600 singleton pregnancies who tested for gestational diabetes by 100g OGTT. They divided into 2 groups equally. Pregnancy outcomes of women who had a single abnormal value were compared with women who had a negative test. Pregnancies with prior cesarean delivery were excluded. Results: Between two groups, the baseline characteristic of the patients were comparable except maternal age [33 (26.37) versus 30 (24.36), p = 0.001] was statistically higher in the study group. Even though the most of adverse pregnancy outcome tend to be higher in study group, but not reach the significance, the rate of cesarean delivery (35.7% versus 25.7, RR 1.39, 95% CI 1.08-1.78), postpartum hemorrhage (38.6% versus 30%, RR 1.29, 95% CI 1.03-1.62) and NICU admission (5.6% versus 1.0%, RR 5.69, 95% CI 1.80-17.96) were higher in study group with significant difference. Caesarean delivery (38.8% versus 28.7%, p = 0.04) and NICU admission (9.5% versus 1.9%, p = 0.0003) were more common if the blood glucose greater than 10 mg/dl normal level. Conclusions: A single abnormal value of 100 g OGTT had significant impact on pregnancy outcome such as increase cesarean section, postpartum hemorrhage and NICU admission.